Strategies for Accelerating Stunting Reduction in Toddlers - Nurdiyan; Sholihah, Qomariatus; Maharani Pertiwi K; Atikawati, Dini (Wacana Journal of Social and Humanity Studies, 2025)
Stunting hurts the physical growth of toddlers. Several contributing factors to stunting include nutritional aspects, exclusive breastfeeding practices, educational levels, maternal knowledge, and a history of low birth weight (BBLR). Efforts to support adequate dietary intake for children require mothers' capabilities in providing caregiving and ensuring a healthy family environment's sanitation. To enhance the handling of stunting, the Indonesian government issued Presidential Regulation No. 72 of 2021, titled "Accelerating the Reduction of Stunting." This regulation emphasizes a holistic, integrative, and quality approach through coordination, synergy, and synchronization among stakeholders. From 2018 to the present, Bojonegoro has recorded a decline in stunting rates. In 2018, the prevalence of stunting was 8.76% (6,941 toddlers), which then decreased to 7.45% (5,868 toddlers) in 2019. The stunting rate continued to decrease in 2020 to 6.84% (5,192 toddlers) and in 2021 to 5.71% (4,277 toddlers). In February 2022, the stunting rate was noted to have further decreased to 5.21% (3,804 toddlers). The latest data from August 2022, based on baby weighing results, recorded 74,626 toddlers with a stunting prevalence of 2,225, or 2.97%. This research aims to plan efforts to accelerate the reduction of stunting rates.   Keywords: strategy, stunting, toddler